Implementasi Pembelajaran Kooperatif dalam Mengoptimalkan Minat Belajar Siswa - F. Lina Azahro; Ma’fiyatun Insiyah (Journal of Primary Education Studies, 2025)
Implementation of cooperative learning in optimizing the learning interest of grade 1 students at MI Darul Hikmah Bantarsoka Banyumas. The background of this research is the low interest in learning of students, which can be seen from the lack of active participation, motivation, and attention of students during the learning process. To overcome this problem, teachers apply various cooperative learning models. This study uses a qualitative descriptive method. Data were collected through observation, interviews with teachers and students, and documentation of learning activities. The results of the study indicate that the implementation of the cooperative learning model used can significantly optimize students' learning interest. Students become more active, dare to express their opinions, are interested in the subject matter, and are able to work together in groups effectively. Teachers are also more creative in organizing learning activities to suit the characteristics of grade 1 students. Cooperative learning not only optimizes learning interest, but also forms students' social skills early on in school, such as helping each other to friends who cannot yet. The models used at MI Darul Hikmah are Learning Together and Numbered Head Together where this learning model can be used as an effective and relevant learning strategy to be applied at the elementary school level.